When Music Speaks: An Acoustic Study of the Speech Surrogacy of the Nigerian Dùndún Talking Drum - Durojaye, Cecilia; Knowles, Kristina L.; Patten, K. Jakob; Garcia, Mordecai J.; McBeath, Michael K. (Frontiers in Communication, 2021)
Yorùbá dùndún drumming is an oral tradition which allows for manipulation of gliding pitch contours in ways that correspond to the differentiation of the Yorùbá linguistic tone levels. This feature enables the drum to be employed as both a musical instrument and a speech surrogate. In this study, we examined four modes of the dùndún talking drum, compared them to vocal singing and talking in the Yorùbá language, and analyzed the extent of microstructural overlap between these categories, making this study one of the first to examine the vocal surrogacy of the drum in song. We compared the fundamental frequency, timing pattern, and intensity contour of syllables from the same sample phrase recorded in the various communicative forms and we correlated each vocalization style with each of the corresponding drumming modes. We analyzed 30 spoken and sung verbal utterances and their corresponding drum and song excerpts collected from 3 native Yorùbá speakers and 3 professional dùndún drummers in Nigeria. The findings confirm that the dùndún can very accurately mimic microstructural acoustic temporal, fundamental frequency, and intensity characteristics of Yorùbá vocalization when doing so directly, and that this acoustic match systematically decreases for the drumming modes in which more musical context is specified. Our findings acoustically verify the distinction between four drumming mode categories and confirm their acoustical match to corresponding verbal modes. Understanding how musical and speech aspects interconnect in the dùndún talking drum clarifies acoustical properties that overlap between vocal utterances (speech and song) and corresponding imitations on the drum and verifies the potential functionality of speech surrogacy communications systems.